Effectiveness of systematic alphanumeric coded endoscopy for diagnosis of gastric intraepithelial neoplasia in a low socioeconomic population - Machaca Quea, Nancy Roxana; Emura, Fabian; Barreda Bolaños, Fernando; Salvador Arias, Yuliana; Arévalo Suárez, Fernando Antonio; Piscoya Rivera, Alejandro (Endoscopy International Open, 2016)
Background and study aims: In the Western world, gastric cancer (GC) usually presents at an advanced stage, carrying a high mortality rate. Studies have reported that 14 % to 26 % of GCs are missed at endoscopy up to 3 years before diagnosis. Systematic Alphanumeric Coded Endoscopy (SACE) has been proposed to improve quality of esophagogastroduodenoscopy (EGD) by facilitating a complete examination of the upper gastrointestinal tract. This prospective cross-sectional study was designed to determine the frequency of gastric intraepithelial neoplasia (GIN) by using the SACE approach in cohort of patients from low socioeconomic level. It also used non-targeted biopsies to evaluate the frequency of premalignant conditions.Patients and methods: A total of 601 consecutive asymptomatic or dyspeptic patients were enrolled between January 2013 and November 2014 at the Huacho regional hospital in Peru. The SACE method proposed by Emura et al, which divides the stomach into 5 regions and 21 areas, was routinely used for diagnosis. Biopsy samples were obtained from any endoscopically detected focal lesion. To evaluate gastric premalignant conditions, 4 non-targeted biopsies were taken. Results: A total of 573 patients were analyzed. The mean age was 57 years, and the female:male ratio was 1.9 : 1. In all cases, complete photo-documentation of the 21 gastric areas was achieved. The overall rate of detection of GIN was 2.8 %. Low-grade displasia, high-grade dysplasia, and adenocarcinoma were found in 13 (2.3 %), 2 (0.3 %), and 1 (0.2 %) of the patients, respectively. The prevalence of at least 1 premalignant condition was 31 %, and helicobacter pylori infection was found in 57 % of patients.Conclusions: Using the SACE approach and with proper training, we have reported herein a high frequency of GIN in patients from a low socioeconomic status. Gastric cancer detection can be improved in a Western endoscopy setting when SACE, as a screening method, is performed by a trained endoscopist.